The Foreign Policy of Irregular Migration Governance: State Security and Migrants' Insecurity in Italy and Australia - Abbondanza, Gabriele (Routledge Advances in International Relations and Global Politics, 2025)
Irregular migration is one of the most momentous phenomena of the 21st century. While it is a life‑changing process for migrants themselves, it also entails a number of significant challenges for destination countries and their local populations. Consequently, irregular migration is now a heavily debated and polarising issue in most receiving states. However, the multiple perspectives on this phenomenon are rarely assessed together, and states’ role in shaping national and international responses remains understudied, which hinders a comprehensive understanding of irregular migration governance. To address this issue, this innovative book investigates irregular migration by concurrently analysing the viewpoints of migrants, states, and their local populations. To that end, it builds on multidisciplinary insights from international relations, migration studies, political science, and other disciplines, and adopts Italy and Australia as two highly relevant yet rarely compared case studies, with a focus on their migratory foreign policies. In arguing for a multidisciplinary and holistic interpretation of irregular migration, it sheds new light on an influential and permanent feature of our times through key theory, security, and policy implications, as well as with relevant proposals. It also provides an assessment of unfolding trends, novel insights, and potential future outlooks based on the latest data and published research. This book is therefore a valuable resource for academics, migration and security professionals, policymakers, diplomats, journalists, and students.